PREVALENCE OF Echinococcucus granulosus IN STRAY AND HOME OWNED DOGS IN ADAMAWA STATE, NIGERIA - Mathias, A.; Pukuma, S. M.; Enock, N. (FUDMA Journal of Sciences, 2023)
Echinococcosis is a zoonotic larval infection affecting both domestic animals and human with serious health and economic impacts. A study to determine the prevalence of E. granulosus was carried out on dogs from six Local Government Areas (LGA) of Adamawa State. Faecal samples from 384 dogs were collected and screened for the presence of E. granulosus cyst microspically. A structured questionnaire was used and obtained native and exotic data from dog owners. Out of the 384 dog faecal samples, 171 had E. granulosus cyst with overall prevalence of 44.5% where Guyuk LGA had highest prevalence of 53.1% and Michika LGA had a lowest prevalence of 39.1%). With regards to gender, male and female dogs had a prevalence of 30.5% and 32.4% respectively. In terms of season, highest prevalence of 42.7% and lowest prevalence of 33.3% was recorded during rainy and dried season respectively with a significant association (P< 0.05). Un-restricted dogs recorded a prevalence of 66.1% and 38.1% was recorded in restricted dogs with significant relationship (P< 0.05). Dogs living in suburban areas and kept for security purposes, hunting or guarding have higher chances of infection. Therefore, right and regular treatment of dogs with praziquantel is highly recommended to reduce risk of E. granulosus transmission to humans.